COGNITIVE VIEW OF BILINGUALISM AND LANGUAGE DOMINANCE IN THE TRANSLATION - Erkinjon Satibaldiyev (Western European Studies, 2024)
This scientific article delves into the intricate dynamics of translation studies, focusing on the cognitive dimensions of bilingualism and language dominance in the translation process. Drawing on historical perspectives, key concepts in translation studies, and cognitive science, the article illuminates how bilingual competence influences the translation of English media texts into Russian and Uzbek. Cognitive benefits of bilingualism, including enhanced flexibility and metalinguistic awareness, are explored alongside the nuanced interplay of language dominance, impacting translation quality. Through a comprehensive analysis, the article reveals that bilingualism is not merely a tool but a cognitive landscape shaping the very fabric of translation, influencing choices, and contributing to the diversity of translated texts
Keywords: bilingualism; language dominance; translation studies